Revolutionizing Finance: The Impact of Blockchain Technology and Crowdfunding - Wodi, Lidya Chatrine; Saksono, Lalang; Nurwulandari, Andini; Sari, Santi Retno (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
This research discusses the revolutionary impact of blockchain technology and crowdfunding in finance. Blockchain technology has been proven to increase authenticity, security, and efficiency in financial transactions, while crowdfunding provides democratic access to capital for innovators and entrepreneurs. The method used in this research is a systematic literature review. In accordance with the SLR process, through rigorous data screening, 44 articles were obtained to be discussed in this theme. Combining these two innovations can create a decentralized ecosystem that supports innovative projects and access to global funding. This research provides insight into how blockchain and crowdfunding can revolutionize the financial industry toward greater sustainability, efficiency, security, and financial inclusion in the future.